ANALYSIS OF MOSQUE MANAGEMENT PERFORMANCE ON ZISWAF FUNDS MANAGEMENT - Ramadhani, Astri; Zuhirsyan, Muhammad; Wathan, Hubbul; Supaino,; Siregar, Rumnasari Khoriyah (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study was conducted to examine the extent to which the management of Nurul Huda Mosque in Medan Marelan administers ZISWAF funds. The research focuses on the case of Nurul Huda Mosque’s management. A qualitative approach was employed, utilizing interviews with mosque administrators and congregants. Both primary and secondary data sources were used, with data collection methods including observation, documentation, interviews, and surveys. The findings reveal that the mosque administrators have managed ZISWAF funds fairly well in terms of implementation and congregational participation. However, the management system is not yet supported by written and structured work procedures. Internal factors such as weak documentation and limited training, as well as external factors including low public trust and high competition from other institutions, serve as the main challenges. The administrators have also begun developing productive activities, such as space rentals, lending of equipment, and parking management, as alternative sources of mosque operational funding.